The Compliance with Health Protocols to Prevent COVID-19 Based on Demographic Characteristics of Population in Isfahan Metropolitan, Iran - Hamid Reza Jamali; Reza Salehzadeh (Vesnu Publications, 2020)
Introduction: Prevention is the best way to effectively deal with COVID-19. Planning to prevent COVID-19 depends on information such as the extent to which health protocols are respected. For this purpose, the present study aimed to assess the extent of compliance with health protocols to prevent COVID-19 incidence given the demographic characteristics of population in Isfahan metroplolitan, Iran.Materials and Methods: A questionnaire was designed by the researcher, and its validity and reliability were confirmed. The questionnaire was distributed through social media, and filled in by 380 Isfahani citizens. Data were analyzed using independent t, Mann-Whitney, and Kruskal-Wallis tests.Results: Women complied with the health protocols significantly more than men (P < 0.001), but the extent of compliance with health protocols showed no significant difference between individuals at different ages (P = 0.473), with different levels of income (P = 0.725), different education levels (P=0.284), and the presence or absence of underlying diseases (P = 0.987). Moreover, in complying with health protocols, less attention was paid to timely replacement of masks.Conclusion: Findings from this study show that how people comply with health protocols depends on factors such as gender. Moreover, the participants attached different levels of importance to different health guidelines.